Pengaruh Persepsi Harga dan Inovasi Produk Terhadap Keputusan Pembelian Hijab Rabbani di Kota Salatiga dengan Religiusitas Sebagai Variabel Pemoderasi - Damayanti, Atika Dela; Cahyono, Edi (As-Syirkah: Islamic Economic & Financial Journal, 2024)
The large Muslim population in Indonesia creates opportunities for entrepreneurs to develop and market their products, especially in the field of Muslim fashion. The aim of this research is to find out how much influence price perceptions and product innovation have on purchasing decisions with religiosity as a moderating variable at the Rabbani company in Salatiga City, especially in the hijab product category. This research is a descriptive quantitative research with primary data obtained from the method of distributing questionnaires to 130 respondents who had purchased hijab products at the Rabbani shop in Salatiga City via Google Form using a purposive sampling technique. Based on the T test and MRA test, it shows that there is a positive and significant influence from the price perception variable on the purchasing decision variable, product innovation on purchasing decisions. There are also positive and significant results from the interaction between price perceptions and religiosity on purchasing decisions and significant positive results from product innovation on purchasing decisions. Therefore, it is important for the Rabbani company to continue to pay attention and maintain consumer satisfaction so that it can continue to compete with similar products.